2021
DOI: 10.1002/cssc.202101575
|View full text |Cite
|
Sign up to set email alerts
|

Electroreductive 5‐Hydroxymethylfurfural Dimerization on Carbon Electrodes

Abstract: The electrochemical conversion of biomass‐based compounds to fuels and fuel precursors can aid the defossilization of the transportation sector. Herein, the electrohydrodimerization of 5‐hydroxymethylfurfural (HMF) to the fuel precursor 5,5’‐bis(hydroxymethyl)hydrofuroin (BHH) was investigated on different carbon electrodes. Compared to boron‐doped diamond (BDD) electrodes, on glassy carbon (GC) electrodes a less negative HMF reduction onset potential and a switch in product selectivity from BHH to the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 47 publications
2
42
0
Order By: Relevance
“…For instance, the contribution of the hydrodimerization in the electrochemical conversion of diluted HMF solutions (0.02 m ) is decreased at more negative potentials than −1.3 V vs. Ag/AgCl over Ag/C electrocatalysts [15] . On carbon electrodes (without any metal species), the same trend is observed, but the production of the dimer is fostered, even with very diluted HMF solutions (e. g., 0.01 m ) [17] …”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…For instance, the contribution of the hydrodimerization in the electrochemical conversion of diluted HMF solutions (0.02 m ) is decreased at more negative potentials than −1.3 V vs. Ag/AgCl over Ag/C electrocatalysts [15] . On carbon electrodes (without any metal species), the same trend is observed, but the production of the dimer is fostered, even with very diluted HMF solutions (e. g., 0.01 m ) [17] …”
Section: Introductionmentioning
confidence: 75%
“…Kloth et al stated that the dimer production for carbon electrodes occurs through an outer-shell mechanism. [17] An increase in the initial HMF concentration favors the dimer production, which can lead to the depletion of protons near the electrode surface, suppressing the formation of H ads , and in turn HER and BHMF production. Chadderdon et al reported that an imbalance between the mass transfer of HMF to the electrode and its consumption rate may deplete the HMF molecules at the surface of the electrode.…”
Section: Electrochemical Characterization and Reaction Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…High BHH formation rates, selectivities, and faradaic efficiencies were observed at low overpotentials where the DHMF formation and HER were still inconspicuous. [97] 2,5-Hexanedione (HD) is a key building block chemical as well as a valuable precursor to produce various biofuels from the ECH of HMF. Roylance and Choi reported the first example of the electrochemical reductive ring-opening of HMF.…”
Section: Electrocatalytic Hydrogenation Pathwaymentioning
confidence: 99%